STUDY OF THE MICROBIOLOGICAL ANALYSES CARRIED OUT AT THE LABORATORY OF A PUBLIC HOSPITAL (CHR AL IDRISSI OF KENITRA) - A. Aziane; M. Elyachioui; A. Elhessni (Journal of Fundamental and Applied Sciences, 2014)
The present work attempts to make a study on the microbiological analyses of pathogens (bacteria or viruses) that are at the origin of the human disease, carried out in the laboratory of microbiological analyses of hospital regional CHR al IDRISSI of Kenitra for a period that extends from the year 2007 to 2009 in order to clarify the methodology of work and the problem of infections in developing countries. Our work is based on the monthly inventory of pathogens (E. Coli, Staphylococcus, Streptococcus, Klebsiella, Enterobacter, Candida albicans, Pseudomonas, Syphilis, hepatitis viruses and HIV) in deferens samples (Urine, Pus, saddle, like and Serum) in patients in relation with total analyses carried out for 3 years. Then we follow their development during this period with the analysis of the results.